Salivary glucose measurement: A holy ground for next generation of non-invasive diabetic monitoring - Anthony Ko; Caizhi Liao (Hybrid Advances, 2023)
Diabetes, a chronic, metabolic disease characterized by elevated levels of blood glucose, over time leads to serious damage to the blood vessels, nerves, eyes, kidneys, and heart. Diabetes affects 422 million people globally, with the majority residing in low- and middle-income nations, and approximately 1.5 million deaths are directly attributed to diabetes annually. Thus, detecting diabetes early is crucial to prevent, monitor, or postpone the advancement of the disease and its associated complications. However, current blood glucose tests for diabetic patients have a significant drawback in that these methods require frequent intrusive blood sampling. Promisingly, salivary analysis has emerged as a non-invasive and convenient alternative glucose monitoring approach for diabetics. In this review, we attempt to chart the landscape of the emerging field of salivary glucose analysis. It is not our intention to wholly review all related work, but rather an assorted selection of seminar reports that exemplify the development trajectory of burgeoning salivary glucose measurement (SGM). The fundamental advantageous nature of SGM as a novel non-invasive method in SGM diagnostic and monitoring fields will be thematically and thoroughly discussed. To inspire next-stage clinical transitional development of this fruitful field, we then explicate challenges that remain to be addressed, and present future directions of salivary glucose analysis.